Rumen Protozoa: The Animals within the Cow - Timothy J. Hackmann (EDIS)
As a cow ambles around and eats from the feed bunk, legions of other “animals” are feeding within the cow’s rumen. Billions of protozoa swim about in a single, 20-gallon rumen, colliding with one another while engulfing feed particles and bacteria. These microbes contribute vitally to rumen fermentation and have both positive and negative impacts on animal performance. This 4-page fact sheet discusses classification, activities, removal, and impacts of protozoa. Written by Timothy J. Hackmann, and published by the UF Department of Animal Sciences, January 2017. Archived September 2020